Parapercis pariomaculata (Perciformes: Pinguipedidae), a new species of sandperch from Lombok and Bali, Indonesia and remarks on the validity of P. quadrispinosa (Weber 1913) - Johnson, Jeffrey W.; White, William T. (Zootaxa, 2012)
A new species of pinguipedid fish, Parapercis pariomaculata, is described from seven specimens collected from Lombok andthe southeast coast of Bali, Indonesia. The species appears locally common, having also been photographed underwater in sev-eral other locations off Bali. It is most similar to Parapercis clathrata in morphology, colouration and meristic values, but isunique among the genus in having a combination of dorsal-fin rays IV, 21, anal-fin rays I, 17, lateral-line scales 57–58, vomerwith 2–4 rows of robust conical teeth, palatines edentate, angle of subopercle produced and with small spinules, 10 abdominaland 20 caudal vertebrae, some nape scales weakly ctenoid in males, pelvic fins not reaching anal-fin origin in males, and colou-ration, including two small black spots on the suborbital, one above the other within a triangular reddish-brown blotch, and thearrangement of black and white blotching and other markings on the caudal fin. Comparison of the mitochondrial cytochrome coxidase subunit 1 (CO 1) genetic marker utilised in DNA barcoding produced a significant genetic divergence of about 12.8%between the new species and its closest congener. A lectotype is designated from the two syntypes of Parapercis quadrispinosa (Weber) which is determined to be a junior synonym of P. clathrata Ogilby.